2019
DOI: 10.3389/fped.2019.00123
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity and Eating Disorders Symptoms: The Role of the Multidisciplinary Treatment. A Systematic Review

Abstract: The prevalence of obesity in children/adolescents has increased worldwide during the past 30 years, becoming a significant public health concern; prevention, and management of pediatric obesity onset is one of the most critical public health goals for both industrialized and developing countries. Pediatric obesity has been identified as a risk factor for various psychopathologies, including eating disorders (ED). Although it has been demonstrated that a comprehensive multidisciplinary treatment (MT), with smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 90 publications
(194 reference statements)
1
27
1
Order By: Relevance
“…Due to this stigmatization, obesity in youth has been shown to be a risk factor for psychopathology, which may manifest itself through body dissatisfaction, shape and weight concerns, and dieting and eating disorder behaviors, such as binge eating and purging [ 4 , 5 ]. Research has also shown that obesity in youth is associated with sneaking and hoarding food, eating when not hungry, and feelings of self-consciousness or embarrassment when eating in front of others [ 6 , 7 ]. Although disordered eating behaviors and eating disorders both encompass a broad array of dimensional maladaptive cognitions and behaviors relating to eating and weight, they differ in their diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this stigmatization, obesity in youth has been shown to be a risk factor for psychopathology, which may manifest itself through body dissatisfaction, shape and weight concerns, and dieting and eating disorder behaviors, such as binge eating and purging [ 4 , 5 ]. Research has also shown that obesity in youth is associated with sneaking and hoarding food, eating when not hungry, and feelings of self-consciousness or embarrassment when eating in front of others [ 6 , 7 ]. Although disordered eating behaviors and eating disorders both encompass a broad array of dimensional maladaptive cognitions and behaviors relating to eating and weight, they differ in their diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention programs that include diet, physical activity (PA), and/or sedentary behavior components are currently the first line of prevention for obesity in adolescent youth [ 6 ]. However, focusing on diet and PA may increase the risk for eating disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would not be uncommon for discrepancies to exist in the quality assessment of an intervention trial between tools. There are two studies in common between our review and that conducted by De Giuseppe et al which may be perceived as having a differing quality ratings, where we have allocated a “neutral” rating and De Giuseppe et al (2019) have allocated a “weak” rating.…”
mentioning
confidence: 99%
“…Interventions within the reviewed papers varied considerably, encompassing SMS support, a Jenny Craig program, and inpatient treatment. De Giuseppe et al also systematically reviewed the impact of pediatric obesity treatment on ED development and rejected meta‐analysis in favor of narrative summary due to significant study heterogeneity. Despite several studies in common, the quality ratings of papers across these two teams differed, with Jebeile et al consistently assessing studies more positively than De Giuseppe et al…”
mentioning
confidence: 99%